Exploring the dynamics of resilience loss and gain in frontier food systems through a systems analysis approach. A conceptual framework. - Minoarivelo, Henintsoa Onivola; Ouedraogo, Yacouba; Craparo, Alessandro Carmelo William (2025)
Frontier food systems, those found in rapidly changing, environmentally fragile, and institutionally uncertain settings, are a fundamental cornerstone of community stability, while simultaneously offering important opportunities for novel, adaptive, and nutritionally robust food systems. These systems, especially in fragile and conflict-affected areas, urban and peri-urban settings, and island contexts, face multiple shocks and long-term pressures. Their ability to cope, adapt, or change is shaped by the combined effects of climate, environmental, economic, and social factors. This report presents a systems-based framework that views food system resilience as a dynamic process emerging from interactions across five key components: external drivers, food supply chains, food environments, consumer behavior, and food system outcomes. The framework links absorptive, adaptive, and transformative resilience capacities to measurable indicators and system processes and outlines an operational approach that combines time-series analysis, network-based modeling, and participatory validation to track resilience loss and gain over time. By combining data analysis with local knowledge, the framework helps identify vulnerabilities and practical pathways to strengthen long-term food system resilience in frontier contexts.